Discovery of mutated oncodriver genes associated with glioblastoma originated from stem cells of subventricular zone through whole exome sequence profile analysis, and drug repurposing - Arnob Sarker; Burhan Uddin; Reaz Ahmmed; Sabkat Mahmud; Alvira Ajadee; Md. Al Amin Pappu; Md. Abdul Aziz; Md. Nurul Haque Mollah (Heliyon)
Glioblastoma (GBM) is one of the most aggressive cancers due to its high mortality rate in spite of intensive treatment. It may be happened because of drug resistance against their typical receptors, since these receptor genes are often mutated by environmental stress. So identifying mutated oncodriver genes which could be used as potential drug target is essential in order to develop effective new therapeutic drugs as well as better prognosis for GBM patients. In this study, we analyzed whole exome sequencing (WES) profiles of NCBI database on GBM and matched-normal (control) samples originated from astrocyte like neural stem cells (NSC) of subventricular zone (SVZ) to explore GBM-causing mutated oncodriver genes, since SVZ is considered as the origin of GBM development. We detected 16 mutated oncodriver genes. Then, filtering by differential co-expression analysis based on independent RNA-Seq profiles of CGGA database revealed 10 genes as dysregulated oncodriver genes. Following that, 3 significantly overexpressed oncodriver genes (MTCH2, VWF, and WDR89) were identified as potential drug targets. Then molecular mechanisms of GBM development were investigated by these three overexpressed driver genes through gene ontology (GO), KEGG-pathways, Gene regulatory network (GRN) and mutation analysis. Finally, overexpressed oncodriver genes guided top-ranked six drug agents (Irinotecan, Imatinib, etoposide, pazopanib, trametinib and cabozanitinib) were recommended against GBM through molecular docking study. Most of our findings received support by the literature review also. Therefore, the findings of this study might carry potential values to the wet-lab researchers for further investigation in terms of diagnosis and therapies of GBM.